Far away from home? Ancient DNA shows the presence of bicolored shrew (Crocidura leucodon) in Bronze Age Denmark - Mahsa Mousavi‐Derazmahalleh; Niels Haue; Marie Kanstrup; Jørgen T. Laursen; Sherralee S. Lukehurst; Jacob Kveiborg; Morten E. Allentoft (Ecology and Evolution)
Abstract An excavation of an Early Iron Age village near Aalborg in Denmark uncovered the jaws and skull fragments from a small mammal that were morphologically identified to the genus Crocidura (white‐toothed shrews). Three Crocidura species are known from prehistoric continental Europe but none of them are distributed in Scandinavia, which is why this surprising finding warranted further analyses. The bone was radiocarbon‐dated to 2840–2750 calibrated years before present (cal. BP), corresponding to the Late Bronze Age and hence earlier than the Iron Age archeological context in which it was found. Using highly optimized ancient DNA protocols, we extracted DNA from one tooth and shotgun‐sequenced the sample to reconstruct a near‐complete mitochondrial reference genome (17,317 bp, 32.6× coverage). Phylogenetic analyses determined this specimen as a bicolored shrew (Crocidura leucodon) but with a phylogenetic position basal to the clade of known sequences from this species. The confirmation of Crocidura presence in Denmark by the Late Bronze Age sheds new light on the prehistoric natural history of Scandinavia. We discuss the implications of this finding from both zoo‐archeological and ecological perspectives. Furthermore, the mitochondrial genome reconstructed in this study offers a valuable resource for future research exploring the genetic makeup and evolutionary history of Eurasian shrew populations.